Enhancing Information Communication Technology Competency in Thai University Student Computer Education Courses - Jutaporn Chardnarumarn; Thiyaporn Kantathanawat; Aukkapong Sukkamart (My University, 2023)
This study’s objectives were to: 1) develop an integrated teaching approach using problem-based learning (PBL) to enhance information communication technology competency (ICTC) in 3 rd -year Thai university Computer Science Studies students, 2) to evaluate the teaching approach, and 3) to compare learning outcomes before and after implementing the approach. The teaching approach comprised eight steps, including 1. Creating a brain-stimulating learning environment, 2. Dividing learners into small groups, 3. Integrating students into groups based on their abilities, 4. Defining problem situations, 5. Structuring the problem-solving processes, 6. Problem linkage, 7. Confronting problems, and 8. Checking for correctness. The learning effectiveness of the ICTC Model’s course implementation had a pre-test mean = 16.70, SD = 1.78, and a post-test mean = 23.00, SD = 2.64, with a statistical t-test value of 8.81. These results indicated that learning outcomes significantly improved after implementing the teaching approach (p<.05) with 20 students. This research contributes to developing an effective instructional method to enhance ICT competencies in Computer Science education.
Keywords: Problem-Based Learning; Structuring; Innovative Teaching Methods